THE PERCEPTION OF PONOROGO MUSLIM SOCIETY IN CHOOSING ISLAMIC BANKING SERVICES - Santoso, Adi; Kristiyana, Naning (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2018)
Research on the perception of Ponorogo Muslim society in choosing Islamic banking services aims to know their perception toward Islamic bank and to determine the financial transaction done by them. This research was conducted in Ponorogo using quantitative descriptive research method. The population is lecturers of STAIN and FAI UNMUH Ponorogo. The sample of the research is 75 respondents. Primary data were collected using questionnaire. Analysis of the data in the field done by using descriptive quantitative format.Perception of both lecturers of STAIN Ponorogo and Islamic Faculty of UNMUH Ponorogo toward Islamic bank is good. It can be seen from the behavior of the consumers / respondents which was influenced by the factor of education in which it is majority dominated bypostgraduate level, culture factor through Islamic culture in work environment both in STAIN and UNMUH Ponorogo, as well as the stimulus of knowing Islamic products that generate the perception as a feedback of the stimulus. Financial transactions carried out by most of the respondents, or 63% of respondents use the services of conventional banks and Sharia banks, while those who use only pure Islamic financial services are just 11 respondents from the whole number of respondents. This has become a new phenomenon found in this study and the respondents use the services of conventional and Sharia banks are based on the rules of the institution where they work.